Stress and Quality of Life in Hypertension Sufferes: A Systematic Review - Surma Elisa Manihuruk; Soenarnatalina Melaniani; Diah Indriani; Andi Safutra Suraya (Indonesian Journal of Global Health Research, 2025)
Hypertension has the potential to cause serious complications such as heart disease, stroke, and kidney failure if not treated properly. Apart from physical factors, hypertension sufferers also often face psychological problems such as stress, which can worsen their condition and affect their quality of life. This study aimed to explore the relationship between stress and quality of life in hypertension sufferers. This systematic review searched for relevant articles using MeSH-based keywords in databases such as Scopus, PubMed, Sage Journal, and Web of Science. The article inclusion criteria were: population: patients with hypertension, intervention: no intervention, comparison: no comparison, results: the article's results showed a relationship between stress and quality of life in people with hypertension. Article quality assessment was carried out using the Joanna Briggs Institute guidelines. Descriptive analysis was carried out using a narrative approach by considering articles published from 2012 to 2024. Based on a literature search, 36229 articles were found with appropriate keywords from Scopus (2578), PubMed (683), Sage Journal (31999), and Web of Science (969). After screening for inclusion and exclusion criteria, 11 articles were identified for inclusion in this review. These eleven articles show that there is a relationship between stress and quality of life in people with hypertension. The importance of a comprehensive approach that considers socioeconomic, demographic, and psychological factors to improve the quality of life of hypertension sufferers.